2010
DOI: 10.1007/s00223-010-9340-9
|View full text |Cite
|
Sign up to set email alerts
|

A Mineral-Rich Extract from the Red Marine Algae Lithothamnion calcareum Preserves Bone Structure and Function in Female Mice on a Western-Style Diet

Abstract: The purpose of this study was to determine whether a mineral-rich extract derived from the red marine algae Lithothamnion calcareum could be used as a dietary supplement for prevention of bone mineral loss. Sixty C57BL/6 mice were divided into three groups based on diet: the first group received a high-fat Western-style diet (HFWD), the second group was fed the same HFWD along with the mineral-rich extract included as a dietary supplement, and the third group was used as a control and was fed a low-fat rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 48 publications
6
47
1
Order By: Relevance
“…Previous studies have shown that this mineral preparation reduced colon polyp formation in mice [21,22], and also inhibited liver tumor formation [23] when included in the diet over the lifespan of the animals. As an unanticipated finding in the pilot study [24], our data suggested that mineral supplementation might also preserve bone structure, at least in female mice. However, in the pilot study, only a small number of animals were included, only a single time-point (15 months) was examined and only effects on long bones were assessed.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Previous studies have shown that this mineral preparation reduced colon polyp formation in mice [21,22], and also inhibited liver tumor formation [23] when included in the diet over the lifespan of the animals. As an unanticipated finding in the pilot study [24], our data suggested that mineral supplementation might also preserve bone structure, at least in female mice. However, in the pilot study, only a small number of animals were included, only a single time-point (15 months) was examined and only effects on long bones were assessed.…”
Section: Introductionsupporting
confidence: 50%
“…Three-dimensional images of the femora in Ringerā€™s solution were obtained using a Ī¼-CT system (eXplore Locus SP, GE Healthcare Pre-Clinical Imaging, London, Ontario, Canada) as previously described and validated [24,27]. Whole bone was scanned and both trabecular and cortical regions of interest (ROI) were reconstructed from the scans as described previously [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice (20 per group) were started at 4 weeks of age on a HFWD, prepared according to the formulation of Newmark et al [17] and used by us in prior studies [13,41ā€“43]. The HFWD is a variant of a standard rodent chow diet, AIN76A, but contains 20% fat from corn oil as compared to 5% in AIN76A [13].…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Dietary supplementation with Aquamin has been shown to preserve bone structure and function in mice on a high-fat Western diet (HFWD). 17 Indeed the bone structure of mice on a HFWD with Aquamin supplementation was superior to that of mice on the standard low fat diet. Thus, indicating that Aquamin supplementation has positive effects on bone health.…”
Section: Introductionmentioning
confidence: 98%